PENGARUH INDIVIDU DAN ORGANISASI TERHADAP DISIPLIN KERJA (Studi Pada PT. Bank â€œXâ€ Cabang â€œYâ€ Malang) - Laily Kristianawati; Heru - Susilo; Taher Al Habsyi (Wacana Journal of Social and Humanity Studies, 2010)
ABSTRACT Â  Work discipline is the condition desired by organization. Work discipline will never be happened automatically, but should be shaped by many factors, both individual and organizational factors. Employee that discipline in their work will give optimal result that supports achievement of companyâ€™s goals. PT. Bank â€œXâ€ Branch â€œYâ€ Malang is a stated-owned corporation and has strategic position in supporting national development. In order to make its function functioned properly, so that PT Bank â€œXâ€ Branch â€œYâ€ Malang has to enhance its organization performance. Organization performance was significantly affected by employee work discipline, while personnel management has heavy duty in creating high-level discipline. This research was explanatory research, with employee of PT. Bank â€œXâ€ Branch â€œYâ€ Malang as the analysis unit. Stratified random sampling technique was used in taking sample, while questionnaire was used to collect data from 50 employees. Variable measurement used in this research was the Likert scale. Data analysis used descriptive and inferential methods. The results showed that: (1) descriptive analysis resulted that variables of employee need (X1), employee capability (X2), work training (X3), compensation type (X4), close-monitoring (X5) and employeeâ€™s work discipline (Y) were perceived by employees properly and occurred as desired. (2) By completely, there was significant influence between independent variables on dependent variable. (3) Partially, variables of employee need (X1), employee work capability (X2), work training (X3), compensation type (X4) and close-monitoring (X5) significantly affected variable of employee work discipline (Y). (4) Regression test result showed that variable of compensation type (X4) has dominant contribution, namely 19,90 percents, on employee work discipline (Y), if been compared with other variables. Variables of compensation type (X4) have dominant contribution in this research. So that there are many things that should be considered by company, namely: 1) variabel of compensation type (X4) essentially on items of incentive giving and amount of insurance guarantee that should be more considered and enhanced because variable of compensation type (X4) had dominant contribution on employee work discipline, of course, and without ignoring other variables. (2) Employee work discipline have shown a properly condition so that should be maintained even enhanced in order to give more maximal value-added for the company. Â  Keywords:Â  work discipline, employee